The Effect of the Application of Discharge Planning on Family Knowledge and Attitudes in Caring for Pediatric Patients after Thyfoid in the Asoka Treatment Room of RSUD Hajjah Andi Depu Polewali Mandar - Yusryah, Yusryah; Wardi, Wardi; Rauf, Abd. (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Discharge planning is planning carried out for patients and families before the patient leaves the hospital with the aim of ensuring that the patient can achieve optimal health and reduce the length of stay and hospital costs. Knowledge is the result of human sensing through a learning process or the result of a person's knowledge of objects through their senses. Attitude is a reaction or response of someone who is still closed to a stimulus. This research aims to determine the effect of implementing discharge planning on family knowledge and attitudes in caring for post-thyphoid pediatric patients in the Ashoka treatment room at Hajjah Andi Depu Polewali Mandar District Hospital. This research is a Quasy Experimental Design with a one-group pre-post test design approach. The sampling method used was purposive sampling, totaling 12 people. The results of the statistical analysis test using the Wilcoxon Signed Ranks Test obtained a p-value of 0.002 for Discharge planning and a p-value of 0.010 for knowledge, the Paired Sample T Test was 0.000, which means it is smaller than α (0.05), so it can be concluded that there is an Influence of the Implementation of Discharge Planning on Family Knowledge and Attitudes in Caring for Post-Thyphoid Child Patients in the Asoka Treatment Room, Hajjah Andi Depu Polewali Mandar Regional Hospital